(untitled) (Research, Society and Development, 2021)
This article aims to show the fundamental role of the pharmacist in the health of the elderly, a class so essential that it is often unattended, the elderly is the age group that most uses medicines in the world so there is a right risk of having drug interaction, since most of them take more than 2 medications a day, the monitoring of a qualified professional is essential to reduce the existing risks, give more confidence to the treatment that the elderly is doing, teach that medications should be taken in the correct time, and that a treatment cannot be stopped in half. Elderly people require a lot of attention and care, as in some situations they do not even know the purpose of the numerous medications they take, causing them not finish the treatment correctly as well as continuous use medications, which should not be forgotten to be taken. The pharmacist is the most qualified professional for this support, we must pay great attention to our erderly, as their power of understanding is often low, a little more patience and caution must be exercised to make drug treatment something that get into their routine to the point where you won’t be forgotten or left out.